Kampf um Vertrauen Die Comcáac von Sonora (Mexiko) unter kolonialer und republikanischer Herrschaft, 1650-1850 - Hölck, Lasse (Historamericana, 2022)
Using the example of the hunter-gatherer group Comcáac ("Seris") and their relationships with the Spanish-Mexican settler society of Sonora (Mexico), trust as the basis of social cohesion is discussed.